Depresyon, anksiyete ve stresin duygusal yeme ile ilişkisinde aleksitiminin aracı rolü - Tüzen, Gizem (İstanbul Medipol Üniversitesi Sosyal Bilimler Enstitüsü, 2019)
Bu çalışmada depresyon, anksiyete ve stresin duygusal yeme ile olan ilişkisinde aleksitiminin aracı rolünün incelenmesi amaçlanmaktadır. Bu doğrultuda cinsiyet, kilo algısı ve beden kitle indeksi değişkenlerinin depresyon, anksiyete, stres, duygusal yeme ve aleksitimi belirtileri üzerindeki etkisinin de incelenmesi hedeflenmektedir. Çalışmaya farklı üniversitelerden 18-38 yaş arası 448 öğrenci katılmıştır. Depresyon, anksiyete ve stres seviyelerini ölçmek için Lovibond ve Lovibond (1995) tarafından geliştirilen Depresyon, Anksiyete ve Stres Ölçeği (DASÖ) kullanılmıştır. Duygusal yeme davranışını ölçmek için Van Strein, Frijters, Bergers ve Defares (1986) tarafından geliştirilen Hollanda Yeme Davranışı Anketi'nin duygusal yeme alt boyutu kullanılmıştır. Aleksitimi seviyesini ölçmek için Bagby, Parker ve Taylor'ın (1994) geliştirmiş olduğu Toronto Aleksitimi Ölçeği (TAÖ-20) kullanılmıştır. Yapılan analizler sonucunda DAS ile duygusal yeme arasında, DAS ile aleksitimi arasında ve duygusal yeme ile aleksitimi arasında pozitif anlamlı ilişkiler bulunmuştur. Yapılan mediatör analizi sonucuna göre aleksitiminin DAS ile duygusal yeme arasında aracı rol oynadığı sonucuna ulaşılmıştır. Yapılan analizlere göre ulaşılan sonuçlar literatüre göre tartışılmış ve gelecek araştırmalar için tavsiyelerde bulunulmuştur.

The aim of this study is to investigate the mediator role of alexithyma in the relationship between depression, anxiety, stress and emotional eating. In this respect, it is aimed to investigate the effects of gender, weight perception and body mass index on depression, anxiety, stress, emotional eating and alexithymia. 448 students whose ages between 18 and 38 from different universities were participated in the study. To assess the levels of depression, anxiety and stress, Depression, Anxiety and Stress Scale (DASS) which was developed by Lovibond, and Lovibond (1995) was used. The emotional eating subscale of the Dutch Eating Behavior Questionnaire (DEBQ), developed by Van Strein, Frijters, Bergers, and Defares (1986) was used to measure emotional eating behavior. In order to measure the level of alexithymia, the Toronto Alexithymia Scale (TAS-20) developed by Bagby, Parker, and Taylor (1994) was used. According to the research results, a significant positive correlation was found between DAS and emotional eating, between DAS and alexithymia and between emotional eating and alexithymia. According to the results of mediator analysis, it was concluded that alexithymia plays a mediating role between DAS and emotional eating. Results, limitations and suggestions of the study were discussed according to the literature.
The mediator role of alexithymia in relation between depression, anxiety and stress and emotional eating
Keywords: Aleksitimi; Anksiyete; Depresyon; Duygusal Yeme; Stres; Alexithymia; Anxiety; Depression; Emotional Eating; Stress